Green Industrial Policies : When and How - Hallegatte, Stephane (World Bank, Washington, DC, 2014)
Green industrial policies can be defined as industrial policies with an environmental goal -- or more precisely, as sector-targeted policies that affect the economic production structure with the aim of generating environmental benefits. This paper provides a framework to assess their desirability depending on the effectiveness and political acceptability of price instruments. The main messages are the following. (i) Greening growth processes to the extent and with the speed needed cannot be done without industrial policies, even if prices can be adjusted to reflect environmental objectives. (ii) "Sunrise" green industrial policies are needed because they support the development of critical new technologies and sectors, bring down costs, and allow for reduced emissions in the short term even in the absence of carbon pricing. (iii) "Sunset" green industrial policies and trade policies may be needed in conjunction with safety nets to make carbon pricing politically or socially acceptable. They can help mitigate the impact of a carbon price on competitiveness and unemployment and smooth the transition by helping industries adjust to the new conditions. (iv) Green or not, industrial policy requires carefully navigating the twin dangers of market and governance failure. The viability of supported technologies and sectors is difficult to assess through a market-test given their dependence on continued environmental policies or pricing -- such as a carbon price. Particular attention must be paid to avoid potential unintended negative effects, such as rebound effects (especially if prices are inappropriate), misallocation of capital, or capture and rent-seeking behaviors.